Iron regulated outer membrane proteins (IROMPs) as potential targets against carbapenem-resistant Acinetobacter spp. isolated from a Medical Centre in Malaysia - Hwa, W.E.; Subramaniam, G.; Mansor, Marzida; Yan, O.S.; Anbazhagan, D.; Devi, S.S. (Medknow Publications, 2010)
In this study, a 29-kDa OMP has been identified to be the major outer membrane protein in A. baumannii / calcoaceticus and loss of this porin and overexpression of IROMPs have contributed to carbapenem resistance. Polyclonal antibodies raised against IROMPs may have a role in antimicrobial therapy in these isolates.